Comparison of Transfemoral Versus Transradial Secondary Access in Transcatheter Aortic Valve Replacement. (March 2020) - Junquera, Lucía; Urena, Marina; Latib, Azeem; Muñoz-Garcia, Antonio; Nombela-Franco, Luis; Faurie, Benjamin; Veiga-Fernandez, Gabriela; Alperi, Alberto; Serra, Vicenç; Regueiro, Ander; Fischer, Quentin; Himbert, Dominique; et al.
Abstract : Background: Transfemoral approach has been commonly used as secondary access in transcatheter aortic valve replacement (TAVR). Scarce data exist on the use and potential clinical benefits of the transradial approach as secondary access during TAVR procedures. The objective of the study is to determine the occurrence of vascular complications (VC) and clinical outcomes according to secondary access (transfemoral versus transradial) in patients undergoing TAVR. Methods: This was a multicenter study including 4949 patients who underwent TAVR (mean age, 81±8 years, mean Society of Thoracic Surgeons score, 4.9 [3.3–7.5]). Transfemoral and transradial approaches were used as secondary access in 4016 (81.1%) and 933 (18.9%) patients, respectively. The 30-day clinical events (vascular and bleeding complications, stroke, acute kidney injury, and mortality) were evaluated and defined according to Valve Academic Research Consortium-2 criteria. Clinical outcomes were analyzed according to the secondary access (transfemoral versus transradial) in the overall population and in a propensity score-matched population involving 2978 transfemoral and 928 transradial patients. Results: Related-access VC occurred in 834 (16.9%) patients (major VC, 5.7%) and were related to the secondary access in 172 (3.5%) patients (major VC, 1.3%). The rate of VC related to the secondary access was higher in the transfemoral group (VC, 4.1% versus 0.9%, P <0.001; major VC, 1.6% versus 0%, P <0.001). In the propensity score-matched population, VC related to the secondary access remained higher in the transfemoral group (4.7% versus 0.9%, P <0.001; major VC, 1.8% versus 0%, P <0.001), which also exhibited a higher rate of major/life-threatening bleeding events (1.0% versus 0%, P <0.001). Significant differences between secondary access groups were observed regarding the rates of 30-day stroke (transfemoral: 3.1%, transradial: 1.6%; P =0.043), acute kidney injury (transfemoral: 9.9%, transradial: 5.7%; P <0.001), and mortality (transfemoral: 4.0%, transradial: 2.4%, P =0.047). Conclusions: The use of transradial approach as secondary access in TAVR procedures was associated with a significant reduction in vascular and bleeding complications and improved 30-day outcomes. Future randomized studies are warranted. Abstract : Supplemental Digital Content is available in the text.